Pelatihan Bahasa Inggris Dasar Bagi Karang Taruna di Kecamatan Sintoga Kabupaten Padang Pariaman - Ance Jusmaya; Okma Permata; Sari Rahayu (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
The tourism industry is currently growing rapidly. The tourism village program, which is currently being promoted by the government, encourages young people who are members of youth organizations to be able to promote tourist attractions in their villages. In a tourism village program, ideally young people among village cadets serve as guides, guides and even determine the success of this program. Youth in Karang taruna need to have basic English for Tourism in order to be able to describe and promote the tourism of the village to tourists who visit later. However, the facts found in the field that there are still many  Karang  taruna members who are unable to communicate  English. They are not at all familiar with English. Based on that phenomenon, this activity aims to  help  introducing and maximizing  basic English learning for Karang Taruna  members in the Sintoga District, Padang Pariaman. The target to be achieved is that the Karang Taruna members of the youth group understand the basics of English and can properly promote tourist attractions in their village. The method used in this community service is a communicative approach method, by training Karang Taruna members to be able to communicate in English contextually. The results of this training show that  the enthusiasm of the Karang Taruna members  to learn and improve their English skills. Their responds are  positive.Next,  it is hoped that this program can be continued regularly in the future